Plant Traits, Environmental Factors, and Pollinator Visitation in Winter-flowering Helleborus foetidus (Ranunculaceae) - SÁNCHEZ-LAFUENTE, ALFONSO M. (Ann Bot, 2005)
• Background and Aims This study examined the effect of plant traits and environmental factors on pollinator visitation in the winter-flowering Helleborus foetidus (Ranunculaceae) in three distant regions in the Iberian Peninsula. • Methods Geographical variation in floral visitor assemblage, plant traits and environmental factors were analysed during the flowering season. • Key Results Differences were found in all plant traits measured (number of open flowers, flower size, number of stamens per flower, and number of nectaries) both within and among regions, and differences among regions in all the environmental factors considered (air temperature, exposure to sunlight, canopy cover, and distance to the nearest neighbour). Differences were also found among regions in the probability that plants would be visited by pollinators. • Conclusions The results show that, although floral display (i.e. number of open flowers on a plant on a given day) consistently explained among-plant differences in visitation rate in all regions, visitation rate was not significantly affected by any other biological or environmental variable. In Helleborus foetidus, then, ‘how’ the plant is would seem to be more important than ‘where’ is it.